THE ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF REGIONAL GOVERNMENT APPARATUSES OF BANDA ACEH - Yunina, Fitri; Lastri, Surna; Agustina, Maya; Yani, Friska (IAIN Lhokseumawe, 2024)
The phenomenon that occurred in 2017 based on the BPK's Opinion on the Financial Report of the Banda Aceh City Government was Fair Without Exception or